Exploring the role of atmospheric cues and authentic pride on perceived authenticity assessment of museum visitors - Loureiro, S. M. C. (International Journal of Tourism Research, 2019)
The current study aims to investigate the relationships between authenticity and related constructs, such as atmospheric cues, place attachment, authentic pride, and word of mouth. We tested the proposed model using a sample of 387 visitors who experienced the National Museum of Ancient Art in Lisbon, Portugal. Atmospheric cues revealed to be a more important driver to perceived authenticity than place attachment. Perceived authenticity seems to be a better predictor of authentic pride than word of mouth. The results allow to highlight several implications and suggestions for further research.